Multi-domain computerized cognitive training program improves performance of bookkeeping tasks: a matched-sampling active-controlled trial - Lampit, Amit; Ebster, Claus; Valenzuela, Michael (Frontiers in Psychology, 2014)
Cognitive skills are important predictors of job performance, but the extent to which Computerized Cognitive Training (CCT) can improve job performance in healthy adults is unclear. We report, for the first time, that a CCT program aimed at attention, memory, reasoning and visuo-spatial abilities can enhance productivity in healthy younger adults on bookkeeping tasks with high relevance to real-world job performance. 44 business students (77.3% female, mean age 21.4 ± 2.6 years) were assigned to either (a) 20 hours of CCT, or (b) 20 hours of computerized arithmetic training (active control) by a matched sampling procedure. Both interventions were conducted over a period of six weeks, 3-4 one-hour sessions per week. Transfer of skills to performance on a 60-minute paper-based bookkeeping task was measured at three time points – baseline, after 10 hours and after 20 hours of training. Repeated measures ANOVA found a significant Group X Time effect on productivity (F=7.033, df=1.745; 73.273, p=0.003) with a significant interaction at both the 10-hour (Relative Cohen’s effect size = 0.38, p=0.014) and 20-hour time points (Relative Cohen’s effect size = 0.40, p=0.003). No significant effects were found on accuracy or on Conners’ Continuous Performance Test, a measure of sustained attention. The results are discussed in reference to previous findings on the relationship between brain plasticity and job performance. Generalization of results requires further study.